Social Grid Agents - COGHLAN, BRIAN ARTHUR; KENNY, EAMONN (IGI Global, 2010)
Computational and Data Grids: Principles, Applications and Design offers critical perspectives on theoretical frameworks, methodologies, implementations, and cutting edge research in grid computing, bridging the gap between academia and the latest achievements of the computer industry. Useful for professionals and students involved or interested in the study, use, design, and development of grid computing, this book highlights both the basics of the field and in depth analyses of grid networks.
Computational and Data Grids: Principles, Designs, and Applications
PUBLISHED
Keywords: SGAs; Social Grid Agents; Grid Computing